(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The article aims to analyze the fragment of an interview, in which certain practices within the judicial institution are described in detail; intervention models that violate the rights of women are observed. Such article forms part of the Master thesis of Social and Cultural Studies: "woman survivors of violence”. A study done in the city of Santa Rosa". It addresses the violence against women from the city of Santa Rosa; its aim is to analyze the experiences and strategies of women who survived the effects of physical and emotional violence caused by their partner (boyfriend, spouse, common-law husband). The article considers the guidelines of qualitative research and the descriptive-explanatory design; such features allow to recover the voices of five women, to show how they define their problem and how they face it, to present the context and the particular characteristics of violence and to identify and explain the individual, community and / or institutional aspects involved in the case.